2021
DOI: 10.18502/ijpa.v16i1.5508
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Immunological Characterization of Somatic Proteins from Adults of Toxocara cati by Proteomics Technique

Abstract: Background: Toxocara cati is considered as one of the main etiological agents of toxocariasis with global and regional importance. As there is no information on proteomics of T. cati, herein, we reported the results obtained by proteomic analysis of somatic proteins extract, using a mass spectrometry (LC–MS/MS) approach. Methods: Somatic extract fractions were separated by two-dimensional SDSPAGE and were electro blotted on to PVDF membranes for immunoblot analysis, then collected the immunogenic spots w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Metabolomics studies were also carried out, where the nonprotein components of the parasite extract were characterized for the three metabolic pathways: fatty acid, amino acid, and carbohydrate metabolism [71]. Soleymani et al [72] through proteomic analyses identified a variety of proteins from the soluble extract of T. c a t i adults, which could have a role in the host-parasite interaction, as well as 10 somatic proteins of this parasite with the capacity to generate an immune response by the host.…”
Section: Possible Variables To Develop In the Constitution Of An Inte...mentioning
confidence: 99%
“…Metabolomics studies were also carried out, where the nonprotein components of the parasite extract were characterized for the three metabolic pathways: fatty acid, amino acid, and carbohydrate metabolism [71]. Soleymani et al [72] through proteomic analyses identified a variety of proteins from the soluble extract of T. c a t i adults, which could have a role in the host-parasite interaction, as well as 10 somatic proteins of this parasite with the capacity to generate an immune response by the host.…”
Section: Possible Variables To Develop In the Constitution Of An Inte...mentioning
confidence: 99%
“…In addition, they could be more reliable for assessment in larger sample size [9,14,15]. The immune reactive bands of T. canis crude antigen were revealed with dog serum and the reactivity properties of somatic proteins of T. cati adult worms were identified using techniques such as proteomics [16][17][18].…”
Section: Introductionmentioning
confidence: 99%